Problem Portraits: Francisco Oller in the Age of US Imperialism - Natalia Ángeles Vieyra (University of Minnesota Libraries Publishing, 2021)
Newly surfaced documents . . . serve to elucidate our understanding of Oller’s artistic endeavors as he navigated the political waters of the US imperialist regime.